Pengaruh Promosi dan Kualitas Pelayanan terhadap Kepercayaan dan Loyalitas Donatur Dompet Dhuafa Riau (The Effect of Promotion and Quality of Service on the Trust and Loyalty of Dompet Dhuafa Riau) - Andrika Saputra; Alvi Furwanti Alwie; Any Widayatsari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to analyze the effect of promotion and service quality on the trust and loyalty of donors to perform Zakat, Infaq, and Alms in Dompet Dhuafa Riau. This research uses a quantitative approach with a survey method of 312 donors of Dompet Dhuafa Riau. The variable measurement uses a Likert scale with weights from 1 to 5. To analyze the effect of variables X1, X2 on Z through Y using statistical techniques path analysis. To test the level of significance using the t-test. This study found promotion had a positive and significant effect on loyalty, service quality had a positive and significant effect on loyalty, the trust had a positive and significant effect on loyalty, the promotion had an effect on loyalty through trust, and service quality had an effect on loyalty through trust.